2012
DOI: 10.4049/jimmunol.1103071
|View full text |Cite
|
Sign up to set email alerts
|

CD23+CD21highCD1dhigh B Cells in Inflamed Lymph Nodes Are a Locally Differentiated Population with Increased Antigen Capture and Activation Potential

Abstract: CD23+CD21highCD1dhigh B cells (Bin cells) accumulate in the LNs draining inflamed joints of the TNFα transgenic (TNFtg) mouse model of rheumatoid arthritis, and are primarily involved in the significant histological and functional LN alterations that accompany disease exacerbation in this strain. Here we investigate the origin and function of Bin cells. We show that adoptively transferred GFP+ sorted mature follicular B (FoB) cells home preferentially to inflamed LNs of TNFtg mice where they rapidly differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 84 publications
(98 reference statements)
5
24
0
Order By: Relevance
“…In order to more specifically test the involvement of TNFR1/2 signals in the generation of Bin cells in the TNF-tg arthritis model, we carried out adoptive transfer of sorted, CFSE-loaded CD23+ CD21/35-low splenic follicular B cells into TNF-tg mice with overt arthritis in the hind and front paws, and then assessed their Bin differentiation in the draining lymph nodes (popliteal, and brachial plus axillary). As previously demonstrated, under these conditions the transferred follicular B cells acquire a Bin phenotype in inflamed LNs within 24–48 hours of transfer, and do so at percentages that closely correlate with the fraction of endogenous Bin cells in the same nodes [6]. Adoptively transferred TNFR1/2KO B cells behaved in the same fashion, showing proportional, quantitative differentiation into Bin cells within recipient nodes (Fig.…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…In order to more specifically test the involvement of TNFR1/2 signals in the generation of Bin cells in the TNF-tg arthritis model, we carried out adoptive transfer of sorted, CFSE-loaded CD23+ CD21/35-low splenic follicular B cells into TNF-tg mice with overt arthritis in the hind and front paws, and then assessed their Bin differentiation in the draining lymph nodes (popliteal, and brachial plus axillary). As previously demonstrated, under these conditions the transferred follicular B cells acquire a Bin phenotype in inflamed LNs within 24–48 hours of transfer, and do so at percentages that closely correlate with the fraction of endogenous Bin cells in the same nodes [6]. Adoptively transferred TNFR1/2KO B cells behaved in the same fashion, showing proportional, quantitative differentiation into Bin cells within recipient nodes (Fig.…”
Section: Resultssupporting
confidence: 72%
“…We have previously shown that differentiation of Bin cells from sorted follicular B cells occurs selectively, quantitatively and rapidly (48hrs) within the inflammatory milieu of TNF-tg LNs draining arthritic joints [6]. We therefore considered whether continuous stimulation with TNF and/or inflammatory stimuli is required to maintain the Bin phenotype.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations